Weighted norms and Volterra integral equations in LP spaces. (1991) - Kwapisz, Jaroslaw
Abstract : A new simple proof of existence and uniqueness of solutions of the Volterra integral equation in Lebesque spaces is given. It is shown that the weighted norm technique and the Banach contraction mapping principle can be applied (as in the case of continuous functions space).